(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this research, using computer simulations, the solar cell (CBTS / CdS / ZnO) was studied by the effect of the thickness and concentration of the absorption layer in it with respect to the properties curve (I - V), the characteristic curve (C - V) and the quantum efficiency curve (QE) of the cell, when thickness of the absorption layer increased It leads to an increase in the short circuit current (Isc), the open circuit voltage (Voc) and the efficiency of the solar cell (Eta) . Also, the quantum efficiency of the solar cell increases with the increase in the thickness of the absorption layer. As for the effect of the carrier concentration of the absorption layer, we found that by increasing the concentration of the absorption layer, (Voc) increases with the increase in the concentration of the doping, while (Jsc) decreases. Therefore, the conversion efficiency depends on the effect of the concentration density. As for the effect of the carrier concentration of the absorption layer on the properties of C-V, it is noticed that increase in capacitance of the solar cell with increasing concentration .